Preference-Based Pricing of the Indonesian JKN-KIS Health Insurance for Urban Middle-Income Self-Funders - Pratikto, Fransiscus Rian (Department of Public Health, Faculty of Sport Science, Universitas Negeri Semarang, 2021)
We determine optimal premiums of the Indonesian JKN-KIS health insurance plans for urban middle-income self-funders based on their preferences. We use the discrete choice experiment to measure preferences assuming a mixed multinomial logit model. By applying the Bayesian method to stated-preference choice data, individual utilities were estimated and subsequently used for deriving price-response functions. We found that more than 90% of respondents prefer the first-class and second-class plans. Accordingly, we set up a pricing optimization formulation for those two plans to maximize total contribution while maintaining the price difference between them and setting the price of the third-class plan as it was. We came up with monthly premiums of Rp290,000 and Rp240,000 for the first-class and the second-class plan, respectively, with an estimated monthly total contribution of Rp1.191 trillion, a 150% increase compared to that of the current pricing. This reveals the opportunity for increasing revenue by implementing finer price differentiation without sacrificing the mission of serving the underprivileged with the third-class plan.